Aplikasi Berbasis Dekstop Untuk Persediaan Bahan Baku Produksi (Study Kasus :PT. Seyon Indonesia) - Eka Chandra Ramdhani; Hotniasi Gaja; Ratnawati Ratnawati (Politeknik Harapan Bersama, 2018)
Basically, the computer functions are generally used as a medium for storing data and in it there are many application programs that can simplify and support a human work. In the warehouse of PT Seyon Indonesia for the process of inventory data management (raw and supporting), reports and data storage is still done manually. The existence of data recording errors and data inaccuracies are very likely to occur in this regard. To help facilitate the management of inventory data (raw and supporting) in the section, the design of the program is the best solution to solve the problems that exist, namely in terms of data processing more accurate because the availability of input form data available and storage media centered in a single database that will make data management of incoming and outgoing goods more effective and efficient. The design of the inventory program (raw and supporting) is made with a simple and interactive appearance but can process data well, so users can easily use it.